Multi-functional polyhedral oligomeric silsesquioxane-functionalized carbon nanotubes for photo-oxidative stable Ultra-High Molecular Weight Polyethylene-based nanocomposites. (February 2016) - Dintcheva, N.Tz.; Arrigo, R.; Carroccio, S.; Curcuruto, G.; Guenzi, M.; Gambarotti, C.; Filippone, G.
Graphical abstract: Highlights: Advanced multi-functional CNTs bearing immobilized phPOSS have been synthesized. UHMWPE/phPOSS- f -CNTs properties are resultant of plasticizing and reinforcing actions. UHMWPE/phPOSS- f -CNTs exhibits excellent photo-oxidative stability. phPOSS gathering at polymer–particle interface is key issue for enhanced stability. Abstract: Nanohybrid (phPOSS- f -CNTs) based on Carbon Nanotubes (CNTs) and Phenyl Polyhedral Olygomenric Silsesquioxane (phPOSS) have been synthesized to be used as multifunctional filler for polymer nanocomposites. The success of the functionalization procedure has been demonstrated via accurate spectroscopic, spectrometric and thermo-gravimetric analyses. The results reveal that a large portion of phPOSS is covalently linked to CNTs, while a small amount of phPOSS remains physically adsorbed due to the strong interactions coming from π electron coupling between the CNTs and phenyl rings in phPOSS. Small amounts (1 wt.%) of phPOSS- f -CNTs have been dispersed in Ultra High Molecular Weight Polyethylene (UHMWPE), aiming at improving the photo-stability of the resulting nanocomposite. The rheological and thermo-mechanical behavior of UHMWPE/phPOSS- f -CNTs nanocomposite reflects two different opposite contributions, namely the reinforcement effect of CNTs and the plasticizing action of phPOSS molecules. Concerning the photo-oxidative behavior, phPOSS- f -CNTs show a remarkable protective ability, which is absolutely much higher than those exerted by CNTs and phPOSS molecules when added one by one. Such unexpected results could be explained considering (i) a synergic effect between phPOSS and CNTs, (ii) the possibility of phPOSS to act at the polymer–nanoparticles interface, which is a critical region for the degradation processes, and (iii) the formation of a phPOSS-rich layer that may hinder the oxygen diffusion within the polymeric matrix.